The significance of the categories of Spinoza’s ethics for cultural historical research La importancia de las categorías de la ética de Spinoza para la investigación histórico-cultura - Fichtner, Bernd (Série-Estudos, 2016)
The starng-point for this presentaon is a joint Brazilian-German research project on “Reading and Wring as a Cultural Praxis of Youth”. This was an empirical qualitative study on the basis of open“dialogical interviews” (Bakhtin) which focused on this praxis of youths. In addition to Bakhtin as amethodological perspective, Lurija’s concept of a “romantic science” became fundamental to ourproject1. The goals of our research were as follows: 1. To understand reading and writing intheirinterrelationship as a specific form of cultural praxis; 2. To contribute by means of research on thisspecific praxis to the theoretical dimensions of the concept of “cultural praxis” as a symbolicallymediated praxis; 3.To better understand – precisely by means of this praxis on the part of childrenand youths – current changes in reading and writing. To this end, we proceeded from the assumption that children and youths have a particular sensitivity for symbolizing their experiences with regard tonew developments in a society2. 4. We intended to concretize these goals in a “cultural comparison”of this praxis on the part of Brazilian and German youths. With the following remarks, we will not be presenting the project in its entirety, its results, or the discussion thereof. Rather, we would liketo discuss one particular aspect in more detail: the problem of cultural diff erences, the explosivenature of which only became evident in the course of the research process.